Does (lack of) sight matter for V1? New light from the study of the blind brain. (November 2020) - Ricciardi, Emiliano; Papale, Paolo; Cecchetti, Luca; Pietrini, Pietro
Highlights: The large-scale brain architecture develops even in the absence of visual experience. The sensory-deprived brain maintains a lifelong sensitivity to environmental inputs. The functional 'fate' of V1 in congenitally blind people is still disputed. V1 may retain most of its intrinsic functioning also in congenitally blind individuals.